Revenir aux activités de base - Garneau, Raymond (Assurances)

(untitled) (HEC Montréal, 1993)
According to Mr. Garneau, if the 1980s were years of growth, merging and diversification, the 1990s will be marked by a return to the basic activities of the corporation, a return to the core business. This rule of conduct is based on the simple fact that if it is possible for a corporation to be good in a number of sectors, it is impossible to excel in all of them at once.